GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENJALANKAN FUNGSI MANAJEMEN (Jurnal Tata Kelola Pendidikan, 2019)
This research is entitled Analysis of Principal Leadership Style in Carrying OutManagement Functions in State Senior High School 1 Baleendah. The purpose of this studywas to describe the tendency of the principal's leadership style in State High School 1Baleendah, Bandung Regency. This research is a qualitative research with a descriptiveapproach. Sources of data in this study were the principal, vice principal of the curriculumfield. deputy principal for student affairs, deputy principal in the field of infrastructure,deputy principal in the field of public relations, teachers, and administrative staff. The datatechnique used interviews, observation and documentation study. Data were analyzed byreducing data, presenting data and drawing data in narrative form. The results showedthat: the leadership style used by the principal of State Senior High School 1 Baleendahtended to use democratic amd participative leadership. 1) The leadership of the principal,including the planning process, tends to use a democratic and visionary leadership style.2) The organizing process tends to be carried out in a democratic and participativeleadership style. 3) The implementation process tends to be carried out with a task-orientedleadership style and human relations that prioritizes cooperative relations and general andpersonal direction and guidance. 4) The process of supervision tends to be carried out withdelegative leadership style by supervising directly and giving trust to subordinates tosupervise so as not to continuously supervise by going around the classroom, overseeingthe performance of teachers and employees.
Keywords: Leadership style; Management Function; Principal